The Entrepreneurship of Peruvian Women: Analysis of Some Cases on The Production of Pisco and The Installation of Family Organic Gardens - Hugo GONZÁLEZ (Communications of International Proceedings, 2023)
The objective of this article is to analyze entrepreneurship in Peruvian women, specifically in the production of pisco and in the creation of organic gardens that have been developed in recent years in order to support the family economy. A study was carried out based on the discourse of the experiences of the main protagonists. It is concluded that the ventures developed have been carried out in a context of scarce economic resources, the leadership of women to undertake, the majority participation of the female gender, the rescue of family traditions, the conservation of the environment since the production is organic which allows a healthy diet. However, there are still difficulties in accessing markets where they sell their products at competitive prices. The Government is providing advice through specialists (in production) and with some financing, but there is still a lack of orientation in the conquest of competitive markets for the sale of production.
Keywords: Entrepreneurship; leadership; family economy; entrepreneurial woman; tradition.